Orchids of the central basin of Siversky Donets in nature and in initial culture - M.B. Gaponenko; Y.V. Minina (Інтродукція Рослин, 2000)
The data on species content, distribution and structure of orchid population in the central basin of Siversky Donets are cited. The results of researches on cultivation and propagation of some orchid species under the condition of M.M. Grishko National Botanical Gardens are considered.